IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN AL-QUR'AN HADITS DI MI BILINGUAL MASLAKUL HUDA LAMONGAN - Nadlir, Nadlir; Nur'aini, Hepy Dwi; Azizah, Ilma Nur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to describe the implementation of an independent curriculum in the subject of Al-Qur'an Hadith in Class 4 of MI Bilingual Maslakul Huda Lamongan. The approach in this research is a qualitative approach with a field research method. The data collection techniques used are observation and interviews. The interview was conducted together with the Al-Qur'an Hadith teacher of grade 4 MI Maslakul Huda. Data in the form of interviews, observations, and observations that have been collected are then analyzed with 3 stages, namely data reduction, data presentation, and conclusion drawing. The results of this study are the implementation of Al-Qur'an Hadith learning in grade 4 MI Maslakul Huda has used teaching modules in the planning process, and the implementation of learning is designed in groups to increase student interaction. At the evaluation stage, all questions used the HOTS type with C4-C6 indicators. The difference in the use of the independent curriculum in general with the bilingual independent curriculum in the Al-Qur'an Hadith subject lies in the use of two languages in learning activities, namely English and Indonesian. Not only in learning activities but student handbooks and questions given to students also use English as a whole.